The place of morphology in learning to read in English. (July 2019) - Rastle, Kathleen
Abstract: Morphology is a major organising principle of English and other alphabetic languages, but has been largely neglected in theories of reading acquisition. In this article, I develop the view that learning to appreciate morphological relationships may be a vital part of acquiring a direct mapping between printed words and their meanings, represented in the ventral brain pathway of the reading network. I show that morphology provides an important degree of regularity across this mapping in English, and suggest that this regularity is directly associated with irregularity in the mapping between spelling and sound. I further show that while children in primary school display explicit knowledge of morphological relationships, there is scant evidence they show the rapid morphological analysis of printed words that skilled readers exhibit. These findings suggest that the acquisition of long-term morphological knowledge may be associated with the ongoing development of reading expertise. Implications for reading instruction are discussed.